1973
DOI: 10.1139/z73-077
|View full text |Cite
|
Sign up to set email alerts
|

Dracunculus lutrae n. sp. (Nematoda: Dracunculoidea) from the otter, Lutra canadensis, in Ontario, Canada

Abstract: Over the interval 1969–1971, carcasses of 1147 mammals taken in Ontario, Canada, were examined for guinea worm. Dracunculus lutrae n. sp., was recovered from otter Lutra canadensis (Schreber). Dracunculus insignis (Leidy 1858) Chandler 1942, was found in raccoon Procyon lotor (L.), mink (Mustela vison Schreber), and fisher (Martes pennanti (Erxleben)). Female worms identified, in the absence of males, as Dracunculus sp. were found in muskrat (Ondatra zibethicus (L.), opossum (Didelphis marsupialis L.), and sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

1991
1991
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…Dracunculus lutrae was first described from specimens collected from otters from Ontario, Canada ( Table 2 ) ( Crichton and Beverly-Burton, 1973 ). A molecular study conducted on Dracunculus from various wildlife species in Ontario, Canada revealed that 18 otters were infected with D. lutrae but two other otters were infected with D. insignis ( Elsasser et al, 2009 ).…”
Section: Dracunculus Species In Mammalsmentioning
confidence: 99%
See 2 more Smart Citations
“…Dracunculus lutrae was first described from specimens collected from otters from Ontario, Canada ( Table 2 ) ( Crichton and Beverly-Burton, 1973 ). A molecular study conducted on Dracunculus from various wildlife species in Ontario, Canada revealed that 18 otters were infected with D. lutrae but two other otters were infected with D. insignis ( Elsasser et al, 2009 ).…”
Section: Dracunculus Species In Mammalsmentioning
confidence: 99%
“…are very similar and molecular characterization is needed for definitive identification. Males are considerably smaller (16–40 mm), but they have several morphological features that can be used to distinguish the different parasite species ( Crichton and Beverly-Burton, 1973 ; Cairncross et al, 2002 ). Unfortunately, males are rarely detected and have never been described for some species.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dracunculus insignis is a parasite known to infect raccoons, dogs, mink, fishers and skunks in the United States east of the Rocky Mountains and in Ontario, Canada ( Crichton and Beverly-Burton, 1973 , Cheng, 1986 ). Experimental infections in ferrets are used as a model for human dracunculiasis ( Eberhard et al., 1988 ).…”
Section: Discussionmentioning
confidence: 99%
“…Experimental infections in ferrets are used as a model for human dracunculiasis ( Eberhard et al., 1988 ). Dracunculus lutrae infects otters in North America ( Crichton and Beverly-Burton, 1973 ). Both species have a similar life cycle to the related the Old World parasite Didelphis medinensis , commonly called the guinea worm, a zoonotic parasite.…”
Section: Discussionmentioning
confidence: 99%